Psychological contract breach and job performance of new generation of employees: Considering the mediating effect of job burnout and the moderating effect of past breach experience - Yu, Dongping; Yang, Ke; Zhao, Xinsi; Liu, Yongsong; Wang, Shanshan; D’Agostino, Maria Teresa; Russo, Giuseppe (Frontiers in Psychology, 2022)
With the intensification of COVID-19 epidemic, it becomes prominent to discuss the issue about the influence of psychological contract breach on job performance of new generation of employees. Based on social exchange theory, fairness theory, and conservation of resource theory, this study constructed a relationship model between psychological contract breach and job performance of new generation of employees with considering the mediating effect of job burnout and the moderating effect of past breach experience. Our hypotheses were tested using data from 235 respondents working in Yunnan Province, China. The results were as follows: first, psychological contract breach had a significant negative effect on job performance of new generation of employees, whether in the whole sample or in two grouped samples; second, both in the overall sample and the grouped sample of state-owned enterprises, job burnout partially mediated the negative relationship between psychological contract breach and job performance of new generation of employees, and past experience of breach positively moderated the negative relationship between psychological contract breach and job performance of new generation of employees; third, in the grouped sample of non-state-owned enterprises, job burnout did not play a significant mediating role in the relationship between psychological contract breach and job performance of new generation of employees, and past breach experience did not play a significant moderating role in this relationship. These findings uncover the psychological mechanism underlying work performance of new generation of employees, and also provide useful theoretical reference for management practices of new generation of employees among different natures of enterprises.